Less is lost [compact disc, unabridged] - Greer, Andrew Sean (Greer, Andrew Sean. Less, 2022)
As awkwardly lovable Arthur Less takes a road trip across America with his dog in his rusty camper van, he ditches his gray suit, grows a mustache, and disguises himself as a cowboy "Unitedstatesian."